Interaction of Silver Nanoparticles with Human Alpha-2-macroglobulin: Biochemical and Biophysical Investigation - Tooba Siddiqui; Mohammad Khalid Zia; Mohammad Muaz; Haseeb Ahsan; Fahim Halim Khan (Cell and BioPharmaceutical Institute, 2022)
Background: Silver nanoparticles (AgNPs) have a broad spectrum of applications in nanoscience and nanomedicine due to their flexible properties, such as antibacterial, antifungal, anti-inflammatory and anti-angiogenic. Present study investigated the interaction of chemically synthesized AgNPs with human major antiproteinase alpha-2-macroglobulin (α2M).Materials and methods: The first step of the study involved the synthesis and characterization of AgNPs using various biochemical and biophysical techniques, such as UV-visible spectroscopy, fluorescence quenching spectroscopy, synchronous fluorescence, and circular dichroism (CD). Different methods were used to explore the primary and secondary structural changes induced in α2M by the binding of AgNPs. Results: The UV-visible spectroscopy revealed hyperchromicity in the absorption spectra of α2M. The presence of a static quenching mechanism was indicated by the temperature-dependent fluorescence spectroscopy. The synchronous fluorescence revealed a change in the microenvironment of the tryptophan residues in α2M. The CD results showed the reduction in β-helical content of α2M. The activity of α2M decreased significantly with the increase of AgNPs concentration.Conclusion: Our result suggests that AgNPs cause modifications in the structure and functional activity of α2M. The interaction of nanoparticles with proteins is important for understanding their potential risks to human health. Keywords: alpha-2-macroglobulin, antiproteinase, silver nanoparticles, fluorescence quenching, FTIR, TEM